Evaluation of Surgical Resection Goal and Its Relationship to Extent of Resection and Patient Outcomes in a Multicenter Prospective Study of Patients With Surgically Treated, Nonfunctioning Pituitary Adenomas: A Case Series. Issue 1 (11th May 2019) - Little, Andrew S; Chicoine, Michael R; Kelly, Daniel F; Sarris, Christina E; Mooney, Michael A; White, William L; Gardner, Paul A; Fernandez-Miranda, Juan C; Barkhoudarian, Garni; Chandler, James P; Prevedello, Daniel M; Liebelt, Brandon D; et al.
Abstract: BACKGROUND: The influence of the surgeon's preoperative goal regarding the extent of tumor resection on patient outcomes has not been carefully studied among patients with nonfunctioning pituitary adenomas. OBJECTIVE: To analyze the relationship between surgical tumor removal goal and patient outcomes in a prospective multicenter study. METHODS: Centrally adjudicated extent of tumor resection (gross total resection [GTR] and subtotal resection [STR]) data were analyzed using standard univariate and multivariable analyses. RESULTS: GTR was accomplished in 148 of 171 (86.5%) patients with planned GTR and 32 of 50 (64.0%) patients with planned STR ( P = .001). Sensitivity, specificity, positive predictive value, and negative predictive value of GTR goal were 82.2, 43.9, 86.5, and 36.0%, respectively. Knosp grade 0-2, first surgery, and being an experienced surgeon were associated with surgeons choosing GTR as the goal ( P < .01). There was no association between surgical goal and presence of pituitary deficiency at 6 mo ( P = .31). Tumor Knosp grade ( P = .004) and size ( P = .001) were stronger predictors of GTR than was surgical goal ( P = .014). The most common site of residual tumor was the cavernous sinus (29 of 41 patients; 70.1%). CONCLUSION: This is the first pituitary surgery study to examine surgical goal regarding extent of tumor resection and associated patient outcomes. Surgical goal is a poor predictor of actual tumor resection. A more aggressive surgical goal does not correlate with pituitary gland dysfunction. A better understanding of the ability of surgeons to meet their expectations and of the factors associated with surgical result should improve prognostication and preoperative counseling.